Liquefaction at Strong Motion Stations and in Urayasu City during the 2011 Tohoku-Oki Earthquake. Issue 1 (March 2013) - Cox, Brady R.; Boulanger, Ross W.; Tokimatsu, Kohji; Wood, Clinton M.; Abe, Akio; Ashford, Scott; Donahue, Jennifer; Ishihara, Kenji; Kayen, Robert; Katsumata, Kota; Kishida, Tadahiro; Kokusho, Takaji; et al.
The 2011 M W = 9.0 Tohoku-oki earthquake generated a large number of unique soil liquefaction case histories, including cases with strong ground motion recordings on liquefiable or potentially liquefiable soils. We have compiled a list of 22 strong motion stations (SMS) where surface evidence of liquefaction was observed and 16 SMS underlain by geologically recent sediments or fills where surface evidence of liquefaction was not observed. Pre-earthquake standard penetration test data and borehole shear wave velocity ( V s ) profiles are available for some stations, but critical information, such as grain size distribution and fines plasticity, are often lacking. In the heavily damaged city of Urayasu, we performed post-earthquake cone penetration testing at seven SMS and V s profiles, using surface wave methods at 28 additional locations to supplement existing geotechnical data. We describe the liquefaction effects in Urayasu, the available site characterization data, and our initial data interpretations.